Design of a Pyrolysis Reactor for Polystyrene Plastic Waste and Numerical Analysis of Temperature and Thermal Stress Distribution Using Ansys - Ali Syamsuddin; Moh Mufti (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The difficult to degrade polystyrene (PS) waste requires efficient pyrolysis technology to be converted into styrene fuel through a 450°C thermal process. This study designed a batch reactor with a conical cylinder (with a diameter of 30 cm, a height of 30 cm, a diameter of 5.08 cm at the base of the cone, and a height of 15 cm, with a capacity of 3 kg of polystyrene) using Ansys for steady-state thermal-structural analysis to determine the best material based on the highest safety factor. The best material was SS 316, with a heating power of 1404 W, which produced the highest temperature distribution of 564,42 ℃ at the surface near the burner. Meanwhile, the internal surface of the reactor had reached 542,88 ℃, which could degrade the polystyrene pyrolysis temperature at an operating temperature of 450 ℃, with an average temperature of 144,4 ℃. The total heat flux on this material is 0.096078 W/mm² in the area of the connection. The safety factor for the reactor with SS 316 material is 1.44 at the maximum Von Misses stress due to the actual thermal gradient of 200,32 MPa.